Analisis Dampak Perspektif Pelaku Usaha dan Tim RPA Ponorogo Terhadap Implementasi Sertifikasi Halal Menggunakan Structural Equation Modeling (SEM) - Negara, Palmadi Putri Surya; Kholis, Muhammad Nur; Nurfadila, Agustin Rani; Wahyudi, Bayu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Products with halal certification have become a decisive factor in consumer purchasing decisions, driven by growing public awareness regarding the halal status of food and beverages. This phenomenon aligns with the implementation of the Halal Product Assurance Law that came into effect on October 17, 2019, which is mandatory for all business entities, including large, medium, small, and micro enterprises. In this context, halal supply chains are partly evaluated based on raw materials that comply with halal rules and requirements established by the Indonesian Ulema Council (Majelis Ulama Indonesia / MUI). This situation encourages culinary business operators in Ponorogo Regency to raise awareness about producing food with Halal certification. Satay, as a culinary product with chicken meat as its main component, requires special attention regarding the perspectives of Chicken Slaughterhouse (RPA) business operators on halal certification, given their position as providers of basic ingredients in the production chain. The implementation of these regulations has generated various responses from entrepreneurs, including RPA managers. This study aims to explore the perspectives of RPA managers on the implementation of halal certification in the Ponorogo area and the factors that influence their views. A qualitative approach was applied in this research, with data collection through direct observation, in-depth interviews, and documentation. The analysis results indicate that external elements play a dominant role in shaping perspectives that subsequently form the basis for individual actions.